(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2024)
To investigate the impact of public and private investment on the market value of companies listed on the Damascus Stock Exchange, controlling for variables such as inflation rate and exchange rate, during the period from 1/1/2010 to 1/12/2021. The research employed a quantitative methodology based on secondary data analysis using the Autoregressive Distributed Lag (ARDL) model for the monthly period from 1/1/2010 to 1/12/2021. Descriptive analysis was conducted using descriptive statistics and graphs to understand the distribution of data and identify outliers. The stability of the variables was then tested using unit root tests (Phillips-Perron) to ensure the validity of using the ARDL model. The ARDL model was then estimated and the long- and short-term relationships between investment, inflation rate, exchange rate, and market value were evaluated. The research findings indicate that investment plays a significant role in shaping the market value of companies listed on the Damascus Stock Exchange. However, this relationship is complicated by the unstable economic environment during the war period. The model analysis shows that public investment promotes long-term growth, while private investment weakens market value. The results also indicate the instability of the relationship in the short term, highlighting the need to improve the economic environment and political stability in Syria to make private investment more attractive and ensure the market’s ability to adapt to economic shocks more effectively.